2005
DOI: 10.1016/j.euje.2004.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Primary left heart malignant fibrous histiocytoma

Abstract: We present the case of a 53 years-old woman presenting with congestive heart failure and pleural and pericardial effusions, in whom transthoracic and transesophageal echocardiography revealed multilocular cardiac tumor involving the left atrium wall, extending into the pericardium. Tumor was excised surgically and proved to be a malignant fibrous histiocytoma, primarily confined to the heart. Despite surgery followed by chemotherapy, the patient died a few months later. This is the 47th case of primary cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, majority of the reported cases showed rapid progression, in terms of recurrence, local infiltration and distant metastasis, with clinical deterioration in a short time and eventual death. [8] Complete surgical resection helps ameliorate symptoms and obtain histologic information.…”
Section: Discussionmentioning
confidence: 99%
“…However, majority of the reported cases showed rapid progression, in terms of recurrence, local infiltration and distant metastasis, with clinical deterioration in a short time and eventual death. [8] Complete surgical resection helps ameliorate symptoms and obtain histologic information.…”
Section: Discussionmentioning
confidence: 99%
“…1 The first case of cardiac MFH was reported by Shah et al 2 in 1978; and 47 cases have since been reported in the literature. 3,4 According to a thorough analysis of the reported cardiac MFH cases by Okamoto et al, the patients' ages ranged from 17 to 77 years, with 62% of the patients female. The most common location of the MFH was the The patient was discharged 15 days after the operation in good condition, and UCG was repeated every 2-3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is the primary tool for the diagnosis of cardiac tumors, but histological findings after surgery are necessary for a definite diagnosis. 4,5 The prognosis of MFH is usually poor. Survival of patients ranges from less than 1 month to 6 years, and averages approximately 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is the primary tool for the diagnosis of cardiac tumors, but histological findings after surgery are necessary for a definite diagnosis. 4,5…”
Section: Discussionmentioning
confidence: 99%